Multifunctional three-dimensional macroporous nanoelectronic networks for smart materials - Liu, Jia; Xie, Chong; Dai, Xiaochuan; Jin, Lihua; Zhou, Wei; Lieber, Charles M. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Seamless and minimally invasive integration of 3D electronic circuitry within host materials could enable the development of materials systems that are self-monitoring and allow for communication with external environments. Here, we report a general strategy for preparing ordered 3D interconnected and addressable macroporous nanoelectronic networks from ordered 2D nanowire nanoelectronic precursors, which are fabricated by conventional lithography. The 3D networks have porosities larger than 99%, contain approximately hundreds of addressable nanowire devices, and have feature sizes from the 10-μm scale (for electrical and structural interconnections) to the 10-nm scale (for device elements). The macroporous nanoelectronic networks were merged with organic gels and polymers to form hybrid materials in which the basic physical and chemical properties of the host were not substantially altered, and electrical measurements further showed a >90% yield of active devices in the hybrid materials. The positions of the nanowire devices were located within 3D hybrid materials with ∼14-nm resolution through simultaneous nanowire device photocurrent/confocal microscopy imaging measurements. In addition, we explored functional properties of these hybrid materials, including (i) mapping time-dependent pH changes throughout a nanowire network/agarose gel sample during external solution pH changes, and (ii) characterizing the strain field in a hybrid nanoelectronic elastomer structures subject to uniaxial and bending forces. The seamless incorporation of active nanoelectronic networks within 3D materials reveals a powerful approach to smart materials in which the capabilities of multifunctional nanoelectronics allow for active monitoring and control of host systems.